The factors that contribute to the cost of raising children among staffs in customer service division of Malaysia Airlines (MAS) at KLIA / Nurul Nadiah Mohd Jamil and Nur Shahira Zarkia @ Zakaria - Mohd Jamil, Nurul Nadiah; Zarkia @ Zakaria, Nur Shahira (2014)
The purpose of this research is to determine the factors that contribute to the cost of raising children among staff in Customer Service Division of Malaysia Airlines at KLIA. There are four factors that will determine the cost of raising children. They are the urbanization, supportive network, attitude and knowledge which are the independent variables for this research. The research is being conducted towards the staff in Customer Service Division of Malaysia Airlines at KLIA. This research is mainly focusing on respondent who have at least children. A list of list name were gathered from Customer Service Division system that consists of 2000 population, however only 1500 of respondents have at least one children. All the information was being collected through the distribution of questionnaire to the staff of Customer Service Division of Malaysia Airlines at KLIA by using the systematic sampling. This research is using the systematic sampling as the sampling technique as it involves drawing every nth element in the population starting with a randomly chosen element between 1 and n. In this research, there are 1500 elements in the population, and researcher only need a sample of 150. Here, the random number was 10. Based on the list name of staff gathered from Customer Service Division who has at least one child, 1500 of list name were divided into 10 persons per chance of being drawn or choose. In short, the list name numbered 10, 20, 30 and so on, would be the sample until 150 respondents were selected. Their feedbacks in answering will be analyzed and summarized by using the Statistical Package for Social Science (SPSS) version 2. The finding of this research revealed that urbanization is the most influential factor that contributes to the cost of raising children.Thus, several recommendations are being made in order to reduce the cost of raising children that need to be considered by parents, government, and industry.